2005
DOI: 10.1038/sj.onc.1208667
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced G1/S transition of G0-arrested estrogen-dependent breast cancer cells is regulated by mitochondrial oxidant signaling

Abstract: We previously reported that 17-b-estradiol (E2)-induced mitochondrial reactive oxygen species (mtROS) act as signaling molecules. The purpose of this study was to investigate the effects of E2-induced mtROS on cell cycle progression. E2-induced cell growth was reduced by antioxidants N-acetyl-L-cysteine (NAC), catalase, and the glutathione peroxidase mimic ebselen. Flow cytometry showed that mitochondrial blockers of protein synthesis (chloramphenicol), transcription and replication (ethidium bromide), and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 38 publications
9
72
0
Order By: Relevance
“…Mitochondria have been found to play a central role in cell cycle regulation (Mitra et al, 2009). Moreover, disruption of the mitochondrial electron transport chain specifically retards the G 1 -to S-phase transition (Felty et al, 2005;Owusu-Ansah et al, 2008). Incidentally, we and others have reported that mitochondria are potential NO targets and affect ATP generation, apoptosis, and cell cycle (Brookes et al, 2000;Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria have been found to play a central role in cell cycle regulation (Mitra et al, 2009). Moreover, disruption of the mitochondrial electron transport chain specifically retards the G 1 -to S-phase transition (Felty et al, 2005;Owusu-Ansah et al, 2008). Incidentally, we and others have reported that mitochondria are potential NO targets and affect ATP generation, apoptosis, and cell cycle (Brookes et al, 2000;Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that growth factors stimulate rapid increase in intracellular ROS that modulate signaling involved in cell growth (Sattler et al, 1999;Felty et al, 2005). The G 1 -to S-phase transition in fibroblasts depends on the intracellular redox status (Menon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling cascades involving protein tyrosine kinases can be enhanced by oxidative inhibition of protein tyrosine phosphatases, and pathways involving NF-kB, JNK, p38 MAPK, and AP-1 are strongly responsive to redox regulation (Droge, 2002). Recent data have suggested that physiological concentrations of E2 trigger a rapid production of intracellular reactive oxygen species (ROS) in endothelial and epithelial cells, and that E2-induced DNA synthesis is at least in part mediated by ROS signaling in these cells (Felty et al, 2005;Felty, 2006). This notion is particularly intriguing, since E2-mediated ROS production in thyroid follicular cells would have two effects: an immediate stimulation of cell proliferation, and a long-term accumulation of oxidative DNA damage.…”
Section: Pi3k-estrogen Cooperation During Proliferationmentioning
confidence: 99%
“…Data represent the mean ± SD of triplicate experiments. (25). The G1/S transition during the cell cycle involves many important cell cycle-related genes such as cyclin D1, p21, and cdk 4; the expression of these genes may be specifically altered in breast cancer cells (26).…”
Section: Effects Of E2 Bpa or MXC On Cyclin D1 And P21 Expression Inmentioning
confidence: 99%